Characterization of the Vaginal Microbiota of Ewes and Cows Reveals a Unique Microbiota with Low Levels of Lactobacilli and Near-Neutral pH - Swartz, Jeffrey D.; Lachman, Medora; Westveer, Kelsey; O’Neill, Thomas; Geary, Thomas; Kott, Rodney W.; Berardinelli, James G.; Hatfield, Patrick G.; Thomson, Jennifer M.; Roberts, Andy; Yeoman, Carl J. (Frontiers in Veterinary Science, 2014)
Although a number of common reproductive disorders in livestock involve bacterial infection, very little is known about their normal vaginal microbiota. Therefore, we sought to determine the species composition of sheep and cattle vaginal microbiota. Twenty Rambouillet ewes and twenty crossbred cows varying in age and reproductive status were sampled by ectocervicovaginal lavage. We amplified and sequenced the V3-V4 region of the 16S ribosomal RNA contents yielding a total of 907,667 high-quality reads. Good's Coverage estimates indicated that we obtained data on 98 +/- 0.01 % of the total microbial genera present in each sample. Cow and ewe vaginal microbiota displayed few differences. Cow microbiota exhibited greater (P ≤ 0.05) α-diversity compared to the ewe microbiota. Both livestock species differed (P ≤ 0.05) from all previously reported vaginal communities. While bacteria were numerically dominant, Archaea were detected in 95% of cow and ewe samples, mainly of the order Desulfurococcales. Both ewes and cows were predominately colonized by the bacterial phyla Bacteroidetes, Fusobacteria, and Proteobacteria. The most abundant genera were Aggregatibacter spp., and Streptobacillus spp. Lactobacillus ssp. were detected in 80% of ewe and 90% of cow samples, but only at very low abundances. Bacteria previously described from culture-based studies as common to the cow and ewe vaginal tract, except for Escherichia, were variably present, and only in low abundance. Ewe and cow pH differed (P ≤ 0.05), with means (+/- standard deviation) of 6.7 +/- 0.38 and 7.3 +/- 0.63, respectively. In conclusion, 16S rRNA sequencing of cow and ewe vaginal ectocervicovaginal lavages showed that cow and ewe vaginal microbiota differ from culture-led results, revealing a microbiota distinct from previously described vaginal ecosystems.